Serum cotinine as a predictor of lipid-related indices in Turkish immigrants with type 2 diabetes: A clinic-based cross-sectional study - Sukhram, Shiryn D.; Zarini, Gustavo G.; Shaban, Lemia H.; Vaccaro, Joan A.; Sukhram, Avinash R.; Huffman, Fatma G. (Frontiers in Medicine, 2023)
Turkish immigrants form the largest ethnic minority group in the Netherlands and show a higher prevalence of (i) cardiovascular disease (CVD), (ii) cigarette smoking, and (iii) type 2 diabetes (T2D) as compared to the native Dutch. This study examines the association of CVD risk factors: serum cotinine, as an indicator of cigarette smoke, and lipid-related indices among first-generation Turkish immigrants with T2D living in deprived neighbourhoods in the Netherlands. A total of 110 participants with T2D, aged 30 years and older, were recruited by convenience sampling in a clinic-based cross-sectional design. Serum cotinine (independent variable) was measured with a solid-phase competitive chemiluminescent immunoassay. Serum lipids/lipoproteins (dependent variables) were determined by enzymatic assays and included: total cholesterol (CHOL), high-density lipoprotein cholesterol (HDL-c), low-density lipoprotein cholesterol (LDL-c), and triglycerides (TG). The Castelli Risk Index-I (CRI-I) and Atherogenic Coefficient (AC) were assessed as dependent variables in multiple linear regression (MLR) models. MLR models were adjusted for all major confounders of cotinine and lipids. The sample size had a mean age of 52.5 years [standard deviation (SD) = 9.21]. The geometric mean of serum cotinine level was 236.63 ng/mL [confidence interval (CI) = 175.89±318.36]. The MLR models indicated that high serum cotinine levels (≥ 10 ng/mL) was positively associated with HDL-c (P = 0.04), CRI-I (P = 0.03), and AC (P = 0.03). This study indicated that lipid ratios of HDL-c, CRI-I and AC are dependent determinants of serum cotinine and higher serum cotinine levels (≥ 10 ng/mL) are associated with worse HDL-c, CRI-I and AC values in participants with T2D. Clinical comprehension of these biochemical indicators (lipids/lipoproteins) and symptomatic results (CVD risk) in individuals with T2D will aid in the intervention (smoking) approach for this vulnerable cohort (Turkish immigrants). Therapy that is targeted to modify this behavioral risk factor may improve cardiovascular health outcomes and prevent comorbidities in Turkish immigrants with T2D living in deprived neighbourhoods in the Netherlands. In the meantime, this report contributes to a growing body of information and provides essential guidance to researchers and clinicians.